School-based health centers and mental health stigma before and during the pandemic - Dara Shifrer; Suzy Fly; Rachel Springer; Xuan Dinh (Elsevier, 2024)
The mental health of children, and especially adolescents, has been a global public health priority for decades. School-based health centers (SBHCs) are health clinics established in close proximity to elementary and secondary schools for the purpose of increasing access to medical, and particularly mental health services, for children and adolescents. Yet, like other health clinics, SBHCs struggle to overcome structural and interpersonal stigma related to mental health conditions and support. Then, the pandemic threatened the sustainability and efficacy of SBHCs just as youth's mental health needs skyrocketed. We use Stangl et al.'s (2019)framework for health-related stigma to analyze data from 36 interviews with SBHC Coordinators in Oregon and their Educator Partners to investigate: 1) What implications does mental health-related stigma have for SBHCs' delivery of mental health services to children and adolescents? 2) How did these factors change during the pandemic? Consistent with Stangl et al.'s (2019) framework for health-related stigma, mental-health-related stigma is evident in this study in terms of the secondary stigma youth are reported to experience from peers and families in terms of visiting a SBHC for mental health services, as well as in limitations in the quantity and quality of resources dedicated to providing mental health services. The pandemic had contradictory effects, both increasing and reducing stigma along two axes: cultural perceptions of mental health problems and telehealth.